Readiness of the national textile industry in facing trade liberalization - Tjia Chen Ming (Central Research Institute for Agriculture (CeRIA), 2022)
This study found that there are three alternative strategies, namely: strength-opportunity, weakness-opportunity, weakness-threats. The support needed by the business world from the government is: R & D development, information on market opportunities, ease of export, sources of funds other than the banking industry to carry out machine restructuring. The textile industry on the world stage is no longer a new figure but an old face. The term textile that we usually hear comes from the Latin word